Microproagation of fluted pumkin by enhanced axilary shoot formation (2002)
In a bid to develop protocols for micropropagation of fluted pumkin (Telfairia occidentalis), single node cuttings of two genotypes, Telfairia occidentalis white and Telfairia occidentalis orange (ToW-1 and ToR-1 respectively) were cuItured in Murashige and Skoog medium but with four different combinations of kinetin and naphthalene acetic acid concentrations. The highest number of nodes per plantlet was obtained in the medium containing l=litre2.0mg/l kinetin which indicates suitability for micropropagation purposes. There was however, lack of root formation: Premature senescence was also significantly predminant in ToR-1 relative to ToW1. Optimum medium for Telfairia micropropagation appears to be genotype